Види родини Orchidaceae урочища “Вовчий” гори Чолієнка (Українські Карпати (Закарпатська обл.)) - Moskalyuk, B.I.; Didenko, S.Ya. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Dactylorhiza maculatа, Epipactis helleborine, Gymnadenia conopsea, Platanthera bifolia, Traunsteinera globosa (Оrchidaceae) – are rare species of Ukrainian flora grown in the conditions of Carpathian mountains from the lowlands to the alpine zone. The study reveals the data about new localities of these species in the Vovchyi locality (Zakarpatsky region). Geographical distribution of species habitat and modern state of populations in new location are described. The main demographical parameters of species in populations are researched. It is found that populations of D. maculata and E. helleborine are normal, homeostatic, complete since they are parts of favorable phytocoenosis and ecotopes, populations of P. bifolia and T. globosa are incomplete and regressive. This is due to the fact that P. bifolia grows in poor phytocoenotic conditions and T. globosа – in poor environmental conditions. In addition, the status of their populations is negatively affected by the regular mowing during the mass flowering period. In spite of incompleteness, the population of G. conopsea is homeostatic and occupies its environmental and phytocoenotic niche.